110k views
0 votes
Simplify the following expression: a + 2c − 5b − c + a − b 2a − 6b + 2c 2a − 6b + c a − 6b + c a − 5b + 2c

2 Answers

6 votes

Answer:

=−ab2+2ac2+2ac+2a−28b+3c

Explanation:

a+2c−5b−c+a−b2a−6b+2c2a−6b+ca−6b+ca−5b+2c

=a+2c+−5b+−c+a+−ab2+−6b+2ac2+−6b+ac+−6b+ac+−5b+2c

Combine Like Terms:

=a+2c+−5b+−c+a+−ab2+−6b+2ac2+−6b+ac+−6b+ac+−5b+2c

=(−ab2)+(2ac2)+(ac+ac)+(a+a)+(−5b+−6b+−6b+−6b+−5b)+(2c+−c+2c)

=−ab2+2ac2+2ac+2a+−28b+3c

Answer:

=−ab2+2ac2+2ac+2a−28b+3c

User Monica Heddneck
by
4.4k points
7 votes

Answer:

B. 2a − 6b + c

Explanation:

Took the test :)

User Bjmc
by
5.6k points